Non-alcoholic fatty liver disease increases the risk of cardiovascular disease in young adults and children: a systematic review and meta-analysis of cohort studies - Liao, Yan-Lin; Zhu, Gen-Yuan; Chang, Cheng (Frontiers in Cardiovascular Medicine, 2024)
Background and aims It is uncertain if there is a link between non-alcoholic fatty liver disease (NAFLD) and cardiovascular diseases (CVD) in young adults and children. To evaluate the potential link between these two conditions, we conducted a systematic review and meta-analysis of cohort studies. Methods A comprehensive search was conducted in PubMed, Web of Science and Embase in order to locate all relevant cohort studies published until August 2023. Random effects meta-analyses were conducted using the generic inverse variance method, with additional subgroup and sensitivity analyses. The Newcastle-Ottawa Scale was employed to evaluate the methodological quality. Results Four cohort studies (eleven datasets) involving 10,668,189 participants were included in this meta-analysis. This meta-analysis demonstrated that NAFLD increases the risk of CVD in young adults and children (HR = 1.63, 95% CI: 1.46–1.82, P < 0.00001). Further subgroup analyses showed that individuals with NAFLD were at a heightened risk of coronary heart disease (CHD) (HR = 3.10, 95% CI: 2.01–4.77, P < 0.00001), myocardial infarction (MI) (HR = 1.69, 95% CI: 1.61–1.78, P < 0.00001), atrial fibrillation (AF) (HR = 2.00, 95% CI: 1.12–3.57, P = 0.02), congestive heart failure (CHF) (HR = 3.89, 95% CI: 1.20–12.61, P = 0.02), and stroke (HR = 1.47, 95% CI: 1.39–1.55, P < 0.00001). The results of subgroup analyses based on the study location, NAFLD definition, and follow-up time also showed consistency with the overall results. Sensitivity analyses showed that our results were robust. All of the included studies were judged to be of medium to high quality. Conclusion Current evidence reveals that NAFLD is linked to an increased risk of major CVD (including CHD, MI, AF, CHF and stroke) in young adults and children. Further research is needed to strengthen this association and provide stronger evidence for primary prevention of CVD in young adults and children with NAFLD. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, PROSPERO registration number: CRD42023457817.